Mechanical performance of lightweight sandwich structures based on trapezoidal corrugated-cores - Noor Zakiah, Md Zaid (2018)
Trapezoidal corrugated-core was fabricated using a 45˚ profiled mould, and used to form a range of lightweight sandwich structures. The 45˚ corrugation angle was chosen since it represents an optimal configuration for all combinations of bending, shearing and strain. The compressive behaviour and failure mechanism in the structures based on two different materials have been investigated experimentally. Trapezoidal corrugated-core is made of carbon fibre reinforced polymer (CFRP) and glass fibre reinforced polymer (GFRP). The aim of this research work is to study the behaviour of trapezoidal corrugated-core subjected to compression stress and to produce a model of mechanical response of trapezoidal corrugated-core with sandwich structures and to study the effect of varying the geometrical parameters on the corrugated-core behaviour. Corrugated composites were designed using hand-layup technique and then bonded to skins using adhesive based on the same material, to produce a range of lightweight sandwich structures. The thickness of the cell walls, number of unit and width cell are used in determining the behaviour of the mechanical structures. The initial failure modes in this corrugated structure are struts buckling, fibre cracking, and delamination in the composite structure. Besides that, the debonding between the skins and the core were also investigated. Compression loading was subsequently performed on the trapezoidal corrugated structure, where the compression strength shows increasing for all the corrugation structure. To simulate the mechanical response of the corrugation structure, Finite Element (FE) models have been generated using ABAQUS. The results were compared to measure the experimental outcome. From the finding, the effects of varying the number of unit cell dominate by CFRP are 3.48 MPa higher than GFRP that 2.08 MPa at three unit cell. It shows that the higher number of unit cells it will affects the composite strength. For the effect of cell wall thickness, the results show that the higher the wall thickness, the higher the compression strength. The compression strength of CFRP and GFRP are 3.48 MPa and 1.74 MPa respectively at 1.75 mm and 1.90 mm thickness. The structures show excellent repeatability in terms of their mechanical response. The mechanical response in compression increases with specimen thickness. Validation Finite Element and experimental data, a very good deal is found between experimental and finite element values. This observation is validated by computing the percentage error between the finite element and the experimental results with average difference around 4.97% in maximum load.